Ethical principles for the care of people with dementia described in the scientific literature: A scoping review protocol - Serrat Fernandez, R; Bobrowicz-Campos, E.; Brandão, T.; Brites; R.; Chacur-Kiss, K.; Cin, A.; Yokuş, S. E.; Ribera, J. F.; Jarašiūnaitė-Fedosejeva, G.; Korkmaz-Yaylagul, N.; Lauridsen, S.; Vila, J. P.; et al. (Ethical principles for the care of people with dementia described in the scientific literature: A scoping review protocol, 2024)
Since individuals with dementia may not always be able to engage in competent decision-making, family and professional caregivers frequently encounter ethical issues in their daily tasks (Hughes et al., 2002; Preshaw et al., 2016). These ethical issues often involve conflicts between moral requirements or ethical claims (Mahon, 2016), such as autonomy and the protection of the well-being of the person with dementia, or the preservation of dignity and the consideration of justice and other relevant normative claims. However, these issues are fundamentally interpretive, and there is no universal consensus on how to address them. Consequently, ethical decision-making in dementia care can be challenging for family and professional caregivers, who may experience moral distress as a result (Hochwald et al., 2021; Pijl-Zieber et al., 2018). Despite its challenges, providing ethical care to people with dementia is of utmost importance, as it not only safeguards their rights and well-being but also reflects society's commitment to upholding specific principles (Barnes & Brannelly, 2008). Ethical care is often considered a cornerstone in ensuring that people with dementia receive the respect and support they deserve. The notion of ethical care inherently relies on normative principles that guide actions, decisions, and behaviors (Brannelly, 2006). These principles serve as moral compasses, offering guidance on what is morally right and just in the context of dementia care. Several recent reviews have addressed ethical issues related to specific aspects of caring for people with dementia, including those associated with different stages of dementia (Harrison Dening et al., 2019), diverse aspects of diagnosis (Merl et al., 2022), sexuality (Mahieu & Gastmans, 2012), or caregiving (van der Geugten & Goossensen, 2020). However, to the best of our knowledge, there has been no review specifically dedicated to exploring the ethical principles and frameworks outlined in the scientific literature on the care of individuals with dementia. In response to this gap, the general objective of this scoping review is to map the ethical principles described in the scientific literature on dementia care and identify any potential ethical frameworks that organize these principles as referenced in the scientific literature.